Сучасний стан та перспективи енергоощадного розвитку інженерних систем овочесховищ в Україні та світі - Суходуб, І. О.; Ільченко, Д. С. (Енергетика і автоматика, 2025)
Preserving the freshness and quality of vegetables is an important task for farmers worldwide, including Ukraine. Amid rising energy prices, the energy efficiency of vegetable storage systems is becoming especially important. Therefore, modern technologies focus on the development of energy-saving technical solutions for vegetable storage facilities aimed at reducing energy consumption and environmental impact. Particular attention is paid to the use of renewable energy sources, automated microclimate control systems and optimization of storage conditions.The paper discusses current trends and prospects for the development of energy-efficient technical systems for vegetable storage facilities in Ukraine and the world. The importance of microclimate optimization for product preservation and minimization of energy costs is emphasized. The study is based on the analysis of scientific publications, regulatory documents and analytical data on ventilation, air conditioning systems and microclimate automation of vegetable storage facilities. A comparative analysis of traditional and modern storage technologies was carried out, including the use of computational fluid dynamics modelling (CFD) to assess the effectiveness of microclimate maintenance systems.It has been identified that the integration of renewable energy sources (PV panels, heat pumps, cold storage systems) significantly reduces the energy consumption of vegetable storage facilities. The use of CFD modelling allows optimization of the parameters of air exchange, temperature and humidity, which helps to reduce product losses. An analysis of modern technologies shows the growing role of intelligent microclimate control systems that automatically adjust the parameters of the air environment and provide optimal conditions for storing vegetables. The introduction of energy-efficient technologies reduces operating costs and minimizes environmental impact. Conceptual approaches to improving the efficiency of vegetable storage based on a combination of CFD modelling, automatic microclimate control systems, and integration of RES have been investigated. Implementation of these approaches will help improve the quality of product storage, reduce energy consumption, and increase the economic efficiency of vegetable storage facilities. Further research in CFD modelling is important to improve airflow, humidity, and temperature distribution technologies, which will increase the efficiency of technical storage systems.Key words: the microclimate of vegetable storage facilities, technical systems of vegetable storage facilities, energy efficiency, CFD modelling, renewable energy sources, ventilation